Reducción de externalidades negativas por aprovechamiento de residuos en el desarrollo de productos: economía circular en la industria olivícola chilena - Kern Falcón, Werther (2022)
The circular economy, as a factor of sustainable development, is an innovative practice of resource allocation that considers the production of goods and the reuse of their waste. Society values the circular economy, since it contributes to the reduction of negative externalities arising from the operation of certain industries that generate waste that is harmful to the environment. In this work, the magnitude of the negative externality represented by the accumulation of the waste called "alperujo" in the olive sector in Chile is evaluated, identifying, and validating new businesses developed from its reuse. For this purpose, a portfolio of viable options for the valorization of alperujo was constituted, based on a contextual analysis, the application of Product-Market Fit and the participation of a focus group, which allowed estimating the reduction of the negative externality, because of the use of alperujo. This industry externality comes from the generation of 120,000 t/year of waste, with an estimated value of USD 10.48 million. The alperujo, in the form of paste or extract, can be incorporated in the production of snacks, antioxidant drinks and yogurt. The sum of the NPV of the three businesses reaches USD 11.63 million, which allows compensating the estimated negative externality with a favorable margin, using 1.8% of the alperujo generated annually in Chile. This study contributes to the validation of the circular business model in a relevant sector of the Chilean export economy.